The Role of Input Modality in Idiom Learning in L1 English and Arabic-speaking Adults and Children and L2 English-speaking Adults - Elotteebi, Ghozayel (2024)
Investigating the learning of multi-word units (MWUs) in various input modes is important because the limited existing research suggests a differential impact of input mode on MWU learning compared to that of single-word items (SWIs). Thus, we cannot assume that findings about SWIs will hold true for MWUs. For example, it has been suggested that listening may play a more significant role in MWU learning than in SWI learning. An open question is how the presence of imagery in multimodal (MM) input may facilitate MWU learning. The few studies examining MWU learning in MM conditions have predominantly focused on non-idiomatic MWUs, such as collocations, which vary considerably in terms of their transparency to idioms. There has also been a tendency in previous research to concentrate on incidental learning from videos. While this research has contributed significantly to our understanding of incidental learning, the use of dynamic visual imagery inherent in videos, complicates our understanding of how images that support meaning interpretation and impact MWU learning. It remains unclear whether the imagery in MM input (pictures + audio) benefits idiom learning or whether listening-only (LO) is as effective. This aim of this thesis was to address these gaps in the field by examining the effect of LO and MM input on idiom learning. The thesis explores the learning of new idioms from LO and MM input in English and Arabic, which is an understudied language. In addition, it looks at learning in an L1 and L2, as well as in adults and children. Target items were novel idioms repeated four times in a fixed pseudo-random order in an informative linguistic spoken context. Following the exposure phase (MM/LO), four immediate tests were administered, assessing the receptive and productive knowledge of meaning and form in the adult studies, and two immediate tests in the child studies assessing the receptive knowledge of meaning and form of the novel idioms. The first study, in Chapter 3 focuses on idiom learning in L1 English adults. The second study, in Chapter 4, replicates Experiment 1 but with L2 English learners. Additionally, in this chapter, the results from Experiment 1 with L1 learners are compared to those of the L2 learners in Experiment 2. The third study, in Chapter 5, replicates Experiment 1 but in a different L1 – Arabic. In this chapter, the results of Experiments 1 and 3 are compared to explore how idiom learning might vary in linguistically unrelated languages. The fourth study, in Chapter 6, investigates idiom learning in L1 English children (aged 5-11 years) and explores how the children learners differ from the L1 English adults in Experiment 1. Finally, the fifth study, in Chapter 6, replicates Experiment 4 but with L1 Arabic speaking children (aged 5-11 years) and compares them to the L1 Arabic speaking adults in Experiment 2. The results of the studies presented in this thesis show that both LO and MM input are effective for L1 English idiom learning, with transparency influencing the learning regardless of input modality. For L2 English speakers, we see that L2 speakers develop knowledge of novel idioms in both modalities, but LO was not effective at the level of form recall. MM input has additional benefits, particularly in meaning gains. Proficiency positively influences learning in both modalities, but the effect of transparency varies across modalities. For the L1 Arabic-speaking adults, the novel idioms were learned in both the LO and MM modalities. However, the supportive images in the MM condition resulted in better performance, suggesting that imagery aids Arabic idiom learning. Transparency had a limited effect and was primarily observed in form recognition. The results of the studies with English- and Arabic-speaking children show that they learn the meanings of novel idioms from LO or MM input but not their forms. The supportive images in the MM condition resulted in better performance among English-speaking children. Age had a limited effect on the idiom learning. Language effects were observed, with English-speaking children sometimes outperforming Arabic-speaking children. The results and implications of each study are considered in the relevant chapter. In addition, the empirical chapters include comparisons of the results from across the chapters. Finally, Chapter 7 provides an overview of the findings and what they tell us more broadly. It also considers theoretical and pedagogical implications of the research in the thesis, some of its limitations and potential future research.